Comparison of ultrasound and magnetic resonance imaging parameters in predicting survival in isolated left‐sided congenital diaphragmatic hernia. (5th May 2014) - Bebbington, M.; Victoria, T.; Danzer, E.; Moldenhauer, J.; Khalek, N.; Johnson, M.; Hedrick, H.; Adzick, N. S.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 609–610